2011
DOI: 10.1183/09031936.00167110
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle effects of electrostimulation after COPD exacerbation: a pilot study

Abstract: Muscle dysfunction is a major problem in chronic obstructive pulmonary disease (COPD), particularly after exacerbations. We thus asked whether neuromuscular electrostimulation (NMES) might be directly useful following an acute exacerbation and if such a therapy decreases muscular oxidative stress and/or alters muscle fibre distribution.A pilot randomised controlled study of NMES lasting 6 weeks was carried out in 15 in-patients (n59 NMES; n56 sham) following a COPD exacerbation. Stimulation was delivered to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
144
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(150 citation statements)
references
References 37 publications
0
144
0
6
Order By: Relevance
“…Troosters et al evaluated resistance training and demonstrated improvement of the 6MWD by a median of 34 m after patient discharge [28]. In a small pilot study (n = 15), Abdeallaoui et al tested neuromuscular electrostimulation and concluded that neuromuscular stimulation is effective in counteracting muscle dysfunction and decreasing oxidative stress [29]. So far, there are no published data analyzing the effects of WBV in patients with COPD exacerbations.…”
Section: Discussionmentioning
confidence: 99%
“…Troosters et al evaluated resistance training and demonstrated improvement of the 6MWD by a median of 34 m after patient discharge [28]. In a small pilot study (n = 15), Abdeallaoui et al tested neuromuscular electrostimulation and concluded that neuromuscular stimulation is effective in counteracting muscle dysfunction and decreasing oxidative stress [29]. So far, there are no published data analyzing the effects of WBV in patients with COPD exacerbations.…”
Section: Discussionmentioning
confidence: 99%
“…However, the demonstrated results provide a basis for implementing NMES in clinical practice in patients with COPD [25][26][27][28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…The sessions were usually performed 5 [25][26][27][28][29] or 4 [7] times a week. The total time of NMES application amounted to 4, 5 or 6 weeks [25][26][27][28][29][30][31][32]. The value of electric current used depended on the specific tolerance of the patient.…”
Section: Application Of Nmes In Patients With Chronic Obstructive Pulmentioning
confidence: 99%
“…Another RCT in COPD patients within the ICU did not show the occurrence of ICUAW in patients treated with NMES [129]. In addition, in the NMES group, the quadriceps muscle strength measured with a dynamometer and the walking distance were increased [130]. Although not performed in patients in the ICU, NMES intervention was shown to increase muscle strength and exercise tolerance [131].…”
Section: Neuromuscular Electrical Stimulationmentioning
confidence: 99%